Glacial and Hydrothermal Sources of Dissolved Iron (II) in Southern Ocean Waters Surrounding Heard and McDonald Islands. Issue 10 (25th September 2020) - Holmes, Thomas M.; Wuttig, Kathrin; Chase, Zanna; Schallenberg, Christina; van der Merwe, Pier; Townsend, Ashley T.; Bowie, Andrew R.
Abstract: The Southern Ocean is the largest region in which iron limits the growth of phytoplankton. However, a phytoplankton bloom thousands of square kilometers in area forms each spring–summer in the Indian sector of the Southern Ocean, both above and to the east of the Kerguelen Plateau. The central region of the Kerguelen Plateau hosts the volcanically active islands, Heard and McDonald (HIMI), the former of which is largely covered by glaciers. The sources and processes governing supply of iron from HIMI to the region are relatively unknown. In the austral summer of 2016, the first voyage to focus on biogeochemical cycling in the HIMI region was undertaken (GEOTRACES process study GIpr05). Using dissolved iron (II) (DFe (II)) and hydrogen peroxide (H2 O2 ) measurements, we are able to resolve iron sources and show that each of the adjacent islands are strong sources of reduced iron, though controlled by different supply mechanisms. At Heard Island, the greatest DFe (II) concentrations (0.57 nmol L −1 ) were detected north of the island. An inverse correlation of DFe (II) concentrations with salinity suggests the origin is from a sea‐terminating glacier on the island. At McDonald Islands, the greatest DFe (II) concentrations (1.01 nmol L −1 ) were detected east of the islands, which, based on DFe (II) profiles from five targeted stations, appear likely to originate from shallow diffuse hydrothermalism. Elevated DFe (II) around HIMI may increase Fe availability for biota and has implications for transport of Fe away from the islands to the broader northern Kerguelen Plateau where the annual plankton bloom is strongest. Plain Language Summary: Phytoplankton form the base of the aquatic food web, produce comparable atmospheric oxygen to terrestrial plants, and help moderate global heating through uptake of CO2 . Thus, it is vital to know what influences phytoplankton growth in the ocean. Along with nutrients such as nitrate and phosphate, phytoplankton require iron for growth. Iron concentrations are very low in the Southern Ocean, limiting the growth of phytoplankton. However, near the Kerguelen Plateau in the Indian sector of the Southern Ocean, a phytoplankton bloom thousands of square kilometers in area forms each spring–summer. There are two volcanically active islands in the central region of the Kerguelen Plateau—Heard and McDonald Islands. Volcanic activity supplies iron in various forms to the ocean, yet these islands have not been studied in detail. Iron (II) is a short lived yet preferred form of iron for phytoplankton in the ocean. Using iron (II), we show that these closely spaced islands supply iron in different ways. Underwater volcanic vents supply iron near McDonald Island, while glacial runoff supplies iron near Heard Island. Knowing these iron sources is essential for understanding what causes this large phytoplankton bloom at the Kerguelen Plateau, an important ecological hotspot and contributor for regulation of atmospheric CO2 . Key Points: Remote Heard and McDonald Islands are distinct iron (II) sources in the Southern Ocean The main iron (II) source at Heard Island is glacial, while hydrothermal vents are the main source of iron (II) near McDonald Islands Dissolved iron (II) and hydrogen peroxide data combined help to resolve iron sources in a well‐mixed and oceanographically complex system